Non-enzymatic urea sensor using molecularly imprinted polymers surface modified based-on ion-sensitive field effect transistor (ISFET) - Rayanasukha, Y.; Pratontep, S.; Porntheeraphat, S.; Bunjongpru, W.; Nukeaw, J. (My University, 2016)
A novel molecularly imprinted electrochemical sensor based on ISFET device has been developed for urea detection sensor. The molecularly imprinted polymers (MIPs) were prepared by photopolymerization on the surface of ISFET device using PMMA and urea as the functional polymer and molecular template, respectively. The fabricated sensors were characterized by potentiometry and UV-Vis spectroscopy. The preparation conditions were optimized for performance of the sensors, i.e. drop-cast volume and incubation time. The MIP modified ISFET sensors has linear range response from 1.0 × 10− 4 to 1.0 × 10− 1 M with the limit of detection of 1.0 × 10− 4 M (S/N = 3). The MIP modified ISFET sensors also exhibit excellent reproducibility, repeatability and stability, as well as high selectivity to urea.
Keywords: Electrochemical sensor; Ion-sensitive field effect transistor; Molecularly imprinted technique; Non-enzymatic sensor; Urea detection